Influence of curing temperature on corrosion protection property of chemically bonded phosphate ceramic coatings with nano-titanium dioxide reinforcement. Issue 2 (1st February 2019) - Liu, Yaxuan; Bian, Da; Zhao, Yongwu; Wang, Yongguang
Abstract: In this study, the chemically bonded phosphate ceramic coating reinforced with nano-titanium dioxide is prepared on the AISI 304L stainless steel by different curing temperatures. The structure evolution, surface roughness, wettability and corrosion resistance of the coating are investigated. The results indicate that with the increase of the curing temperature, the main curing reactions become different, resulting in different reactants as the bonded phase. When the curing temperature increases, the bonded phase translates from aluminum hydrogen phosphate hydrate (AlH3 (PO4 )2 ·3H2 O) phase to berlinite (AlPO4 ) phase, leading to the increase of the corrosion protection property of the coating. That is because berlinite phase can provide a strong bond between ceramic particles and enhance the strength of the coating. Moreover, berlinite phase possesses the low density and more likely distributes on the surface of the coating, which can more effectively protect the stainless steel free from chloride ions destruction. In addition, berlinite phase also increases with the introduction of nano-titanium dioxide. However, compared with nano-titanium dioxide, the curing temperature can better promote the formation of berlinite phase. Therefore, the curing temperature more contributes to the wettability and corrosion protection property of the coating.